Navigational, Historical, and Environmental Perspective of Charlotte County Waterways - David A. Fann; Robert A. Swett; Elizabeth Staugler (EDIS)
SGEB-63, a 2-page full-color map and guide by David A. Fann, Robert A. Swett, and Elizabeth Staugler, uses natural-color aerial photographs, along with historic pictures and maps, to help visitors and residents enjoy and appreciate what they can see and access from recreational vessels. Published by the Florida Sea Grant Program, September 2008.